2019
DOI: 10.1029/2018je005805
|View full text |Cite
|
Sign up to set email alerts
|

Solar Wind Implantation Into the Lunar Regolith: Monte Carlo Simulations of H Retention in a Surface With Defects and the H2 Exosphere

Abstract: The solar wind implants protons into the top 20–30 nm of lunar regolith grains, and the implanted hydrogen will diffuse out of the regolith but also interact with oxygen in the regolith oxides. We apply a statistical approach to estimate the diffusion of hydrogen in the regolith hindered by forming temporary bonds with regolith oxygen atoms. A Monte Carlo simulation was used to track the temporal evolution of bound OH surface content and the H2 exosphere. The model results are consistent with the interpretatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
81
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 47 publications
4
81
0
Order By: Relevance
“…At Reiner Gamma, the field strength is comparable to Gerasimovich, yet Reiner Gamma shows a weaker difference in water supression. We attribute this weaker difference due to the slightly lower latitude of Reiner Gamma (7°N vs 22°S), where warmer temperatures will reduce the background water (Benna et al, ; Farrell et al, ; Hendrix et al, ; Jones et al, ; Li & Milliken, ; Tucker et al, ; Wöhler, Grumpe, Berezhnoy, & Shevchenko, ).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…At Reiner Gamma, the field strength is comparable to Gerasimovich, yet Reiner Gamma shows a weaker difference in water supression. We attribute this weaker difference due to the slightly lower latitude of Reiner Gamma (7°N vs 22°S), where warmer temperatures will reduce the background water (Benna et al, ; Farrell et al, ; Hendrix et al, ; Jones et al, ; Li & Milliken, ; Tucker et al, ; Wöhler, Grumpe, Berezhnoy, & Shevchenko, ).…”
Section: Discussionmentioning
confidence: 95%
“…Lunar surface water was then discovered with infrared data from spacecraft measurements (Clark, ; Pieters et al, ; Sunshine et al, ) and later on was confirmed with ground‐based telescope observations (Honniball et al, ); this water is stable in sunlight at middle to high latitudes (e.g., Clark, ; Honniball et al, ; Pieters et al, ; Sunshine et al, ). A major formation mechanism of this type of lunar surface water is attributed to solar wind implantation (Bandfield et al, ; Clark, ; Hendrix et al, ; Jones et al, ; Li & Milliken, ; McCord et al, ; Pieters et al, ; Sunshine et al, ; Tucker et al, ; Wöhler, Grumpe, Berezhnoy, & Shevchenko, ). Water was also directly observed in the Lunar Crater Observation and Sensing Satellite ejecta plumes at Cabeus crater (Colaprete et al, ; Gladstone et al, ; Hayne et al, ; Schultz et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Usually, the sources and sinks for the H atoms are assumed to be related to the surface chemistry [36] caused by solar wind protons which are implanted in the surface regolith, where they diffuse and degas to the exosphere mainly as H 2 molecules [21,42]. A number of exospheric models and computational simulations have been developed to explain these highly complex and interrelated source and loss processes to understand the composition of Mercury's exosphere [51,25,35,52,24].…”
Section: Discussionmentioning
confidence: 99%